Revealing The Religiosity in Sedulur Sikep Macapat Songs - Retno Hendrastuti (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
Sikep society is known as one of Javanese cultural heritage keepers. Moreover, the society has unique religiosity attitudes that are somehow it misunderstood as disobedience. This research tries to dig the religiosity attitudes reflected on Sikep society’s Macapat songs, especially their focuses and objects. The analysis used appraisal language theory as the approach. The data of the research are words, phrases, or metaphors that reflect attitude in the texts of Sikep society’s macapat songs. The result of the study showed that thereare only two dimensions of religiosity attitudes found in Sikep society’s Macapat song, those are beliefs and values. The value of religiosity reflected on appreciation and judgment; the belief of religiosity consisted of appreciation, judgment, and affect. The objects of religiosity attitudes in the Sikep society’s macapat songs include people (Sikep society, Ki Surantika, man, the children of Sikep society, government, and the ancestors), and something that is humanized (intention, body and soul). The focus of positive moral attitude involves all words, phrases, and metaphor that reflected the principles, prohibitions, ideals; the focuses of negative moral attitude expressed the negative attitudes and behaviors that they proposed to be avoided. Here, the dominant positive attitudes showed their social life. Then, the only two dimensions of religiosity indicate the lack of restricted rules and ritual applied in their religious life.